2014
DOI: 10.5539/ies.v7n2p117
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Acquisition of Employability Skills by Students of Selected Technical Secondary School in Malaysia

Abstract: The main purpose of the study was to assess the acquisition of employability skills by vocational students in Malaysia. A total of 214 students participated in the study. We used the SCANS instrument to assess vocational students' employability skills. The overall mean of vocational secondary students' employability skills was 3.81 (SD = 0.34). Students' employability skills were found to be correlated with gender (r pb = -.172, p = .012), industrial training (r pb = .137, p = .046), involvement in extracurric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Self-concept is an essential factor in the formation of employability within the school environment (Dania, Bakar, & Mohamed, 2014). Numerous researchers have found that self-concept is related to employability (Wu, Tsai, & Chen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-concept is an essential factor in the formation of employability within the school environment (Dania, Bakar, & Mohamed, 2014). Numerous researchers have found that self-concept is related to employability (Wu, Tsai, & Chen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another related issue is the type of analysis has become one of the limitations of the study. Although most studies are conducted using quantitative (Ismail, 2011;Chandrakumara, 2015;Kalbande & Handa, 2015;Yusof, Mustapha, Mohamad & Bunian, 2012;Xu & Zhang, 2015& Dania, Bakar & Mohamed, 2014 but qualitative method has become an interest among researchers (Lorraine & Sewell, 2007;Ismail & Mohammed, 2015;Su & Zhang, 2015). The quantitative aspect focuses on multiple linear regressions that are widely used in predicting the said variable (Dania et.…”
Section: Abstract: Employability Skill Engineering Technology Multimentioning
confidence: 99%
“…The increasing competition for employment emphasizes the importance of the employability skills [14]. Danial and Mohamed [15] identified that employability skills are essential across all areas and types of employment. Higher education institutions (HEIs) have also considered employability skills essential to secure entry level jobs [1,16].…”
Section: A Employability Skillsmentioning
confidence: 99%